PENGARUH BRAND IMAGE, PERCEIVED QUALITY DAN PERCEIVED PRICE PADA KEPUTUSAN PEMBELIAN PRODUK HYPEBEAST MEREK NIKE - Islami, Muhammad Dendy Pradana; Nugroho, Dian Ari (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2022)
This study aims to determine the effect of brand image, perceived quality, and perceived price on purchasing decisions for Nike brand hypebeast products in the group selling hypebeast goods on line applications. The effect to be proven is the influence of the independent variables individually on the dependent variable. This type of research is explanatory research to explain the relationship of two or more symptoms or phenomena. This study used a sample of 131 respondents obtained through the distribution of online questionnaires. Sampling using non-probability sampling technique and purposive sampling method with the characteristics of respondents who are members of the buying and selling group of hypebeast products in the online application and have a minimum transaction of IDR 2,000,000 and are over 17 years old. This research technique uses the IBM SPSS Statistics version 25 program. The results of this study indicate that perceived brand image affects purchasing decisions on Nike hypebeast products in the line app buying and selling group, and perceived quality affects purchasing decisions, while price perceptions affect buying interest.